Meta-Analysis: Factors Related with Obesity in Adolescents - Karismatika Surya Gumilar; Betriza; Nurcahyo Aji Legowo; Bhisma Murti; Ayu Novita Wulandari (Journal of Epidemiology and Public Health, 2024)
Background: Obesity is excess body weight above the normal BMI limit. This can be experienced by anyone, starting from children, productive teenagers who do not maintain a healthy lifestyle, which can cause premature death. There are various factors that cause obesity from several research findings. This study aims to analyze and estimate factors that influence the risk of obesity in adole-scents.Subjects and Method: This research is a systematic review and meta-analysis with PRISMA and PICO diagrams. Population= teenagers. Intervention= strong physical activity, high income, female gender, strong consumption of fruit, and high maternal education. Comparison= weak physical activity, low income, male gender, weak consumption of fruit, and low maternal education. Result= obesity. The search for this article came from databases namely PudMed and Science Direct. The article keywords used are "physical activity" AND "Income" AND "fruit consumption" AND "mater-nal education" AND "obesity" AND "young factor". The articles included in this research are full paper articles, cross-sectional study design, publication year range 2013-2023, and the magnitude of the Adjusted Odds Ratio relationship. Articles were filtered using the PRISMA flow diagram and analyzed using the Review Manager 5.3.Results: There are 10 articles with cross-sectional studies that show the risk of obesity is signifi-cantly influenced by high income by 2.04 times (aOR= 2.04; 95% CI=0.97 to 4.30; p= 0.060), female gender by 2.28 times (aOR= 2.28; 95% CI= 1.64 to 3.17; p<0.001), strong fruit consumption was 2.11 times (aOR= 2.11; 95% CI= 1.30 to 3.44; p= 0.003), and high maternal education was 1.64 times (aOR=1.64; 95% CI= 1.10 to 2.45; p= 0.020) and the influence of weak physical activity which is 0.59 times the risk of obesity with statistically significant results (aOR= 0.59; 95% CI= 0.41 to 0.83; p=0.003).Conclusion: Risk factors that influence obesity in adolescents include high income, female gender, fruit consumption, high maternal education, and weak activity. Keywords: Obesity, risk factors, health problems, teenagers.